If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(p + -8) = 100 Reorder the terms: -4(-8 + p) = 100 (-8 * -4 + p * -4) = 100 (32 + -4p) = 100 Solving 32 + -4p = 100 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + -4p = 100 + -32 Combine like terms: 32 + -32 = 0 0 + -4p = 100 + -32 -4p = 100 + -32 Combine like terms: 100 + -32 = 68 -4p = 68 Divide each side by '-4'. p = -17 Simplifying p = -17
| 1.7x+10x-12x= | | 5.125(6x+8)+3x=5x+25 | | 1+8x=7x+7 | | 8t+4t= | | z-9=1 | | 6x-5=.5x-3 | | (v-7su^2)(v+su^2)=0 | | 3x+x+4=18+x | | -4-6y=21 | | 9sin^2x=4 | | 25=-6t^2+30t+1 | | 57=2(6)+2w | | 60-3n=n | | 12(6x+8)+3x=5x+25 | | 7+x-5=8 | | 88=5w+13 | | (b-2ya^2)(3b-3ya^2)=0 | | 3+5.3x=1 | | -6n-152=-26 | | 7h-4=24 | | 2x+4y^2-6y^2-9+1-x+3x= | | -4c+4-2x=-2(3x-2) | | 4(8x-7)-10(10-8x)+3(-3x+9)=-8(6-7x) | | (9x-31)+(7x-2)+(4x+33)=360 | | 48+(9x-3)=90 | | 2(x-6)-5=2(x-7)-3 | | 2*(10+9m)= | | 8(-6b-1)=-104 | | -6x+5y=25 | | -4x=24x+11 | | (a^2+3sv)(3a^2-sv)=0 | | 3(5x-7)-3(9-6x)+9(-8x+3)=-8(9-5x) |